Comparison of Chest X-Ray Findings Between Primary and Secondary Multidrug Resistant Pulmonary Tuberculosis - Ricky Septafianty; Anita Widyoningroem; M. Yamin S. S; Rosy Setiawati; Soedarsono (HM Publisher, 2021)
Introduction: Radiological imaging has a key role in multidrug-resistant (MDR) pulmonary tuberculosis (TB) screening and diagnosis. However, new cases of MDR pulmonary TB are often overlooked; therefore, its transmission might continue before its diagnosis. The most widely used and affordable radiological modality is a chest radiograph. This study aims to describe the characteristics of primary and secondary MDR pulmonary TB chest x-ray findings for differential diagnosis. Methods: This study was an analytic observational study with a retrospective design. Researchers evaluated medical record data of primary and secondary MDR pulmonary TB patients who underwent chest x-ray examinations. The patient's chest x-rays were then evaluated. Evaluated variables were lung, pleural, and mediastinal abnormalities and severity category. Results: The most common chest x-ray finding in primary MDR pulmonary TB was consolidation (96.2%), which was mostly unilateral (52.0%), accompanied by cavities (71.2%), most of which were multiple (83.8%) with a moderate category of severity. The most common chest x-ray finding in secondary MDR pulmonary TB was consolidation (100%), which was mostly bilateral (60.4%), accompanied by cavities (80.2%), most of which were multiple (90.1%) with severe category of severity. Pleural thickening (47.5%) was also found. Conclusion: There was a significant difference between primary and secondary MDR pulmonary TB in terms of mild severity category, and pleural thickening. Mild severity category is mostly found in primary MDR-TB and pleural thickening is mostly found in secondary TB.